High anxieties : cultural studies in addiction - Brodie, Janet Farrell; Redfield, Marc, 1958- (University of California Press, 2002)
High Anxieties explores the history and ideological ramifications of the modern concept of addiction. Little more than a century old, the notions of "addict" as an identity and "addiction" as a disease of the will form part of the story of modernity.